Ajami in West Africa - Souag, Lameen (AAeO - Afrikanistik-Aegyptologie-Online, 2011)
West Africans throughout the region have creatively adapted the Arabic script to write non-Arabic languages, a form of literacy known as Ajami which remains widespread today despite little or no government support. The variety of methods used to extend the Arabic script to fit other phonological systems are of particular interest: methods that appear unmotivated from a purely linguistic perspective can readily be explained as rational adaptations to the parallel educational system in which Ajami is typically learned, an issue often not taken into account in orthography planning.